Effect of Solvent Variations in the Alcothermal Synthesis of Template-Free Mesoporous Titania for Dye-Sensitized Solar Cells Applications - Zalas, Maciej; Wawrzyńczak, Agata; Półrolniczak, Paulina; Sobuś, Jan; Schroeder, Grzegorz; Jurga, Stefan; Selli, Elena (PLOS ONE, 2016)
A series of 14 mesoporous titania materials has been synthesized using the simple alcothermal template-free method and various alcohols, such as methanol, propanols and butanols, as solvents. All materials were characterized by both wide and small angle XRD, which exhibited the anatase phase with short-range ordered mesoporous structure that is still forming during post synthetic temperature treatment in most of the investigated materials. Nitrogen adsorption–desorption isotherms confirmed the mesoporous structure with surface area ranging from 241 to 383 m2g- 1 and pore volumes from 0.162 to 0.473 m3g-1, UV-Vis diffuse reflectance showed the redshift of the absorption edge and the bandgap decrease after post synthetic calcination of the materials presented. The TEM, FT-IR, DTA and TG measurements have been made to well characterize the materials synthesized. The mesoporous samples obtained were applied as anode materials for dye-sensitized solar cells and showed good activity in photon-to-current conversion process with efficiency values ranging from 0.54% to 4.6% and fill factors in the 52% to 67% range. The photovoltaic performances were not as high as those obtained for the materials synthesized by us earlier employing ethanol as a solvent. The differences in the electron lifetime, calculated from electrochemical impedance spectroscopy results and varying between 4.3 to 17.5 ms, were found as a main factor determining the efficiency of the investigated photovoltaic cells.